Redesain Website Rumah Tradisional Jawa pada Alun-Alun Project: Rumah Tradisional Jawa - Majestic Tampak Pagalla; Gloria Virginia; Aditya Wikan Mahastama (Fakultas Teknologi Informasi, 2026)
The Alun-Alun Project website serves a strategic role as a primary documentation and reference source for university students studying the architectural richness of traditional Javanese houses; however, its effectiveness is currently hindered by suboptimal User Interface (UI) and User Experience (UX) issues. Initial observations indicate that the current visual presentation fails to adequately represent modern aesthetics and features a confusing navigation structure, which impedes the effective delivery of philosophical information and undermines the website’s credibility as an accessible academic resource. Consequently, this study aims to execute a redesign by implementing the User Centered Design (UCD) method to ensure the design process prioritizes the specific needs of students. Through comprehensive data collection and direct user interaction, this research improves the information architecture and navigation flow to align with users' academic behavioral patterns. The result of this study is the realization of a new interface design developed from requirements analysis to final design solutions, where the UCD implementation proved effective in not only updating visual appeal but also rectifying system usability structures. It is concluded that this redesign successfully addresses previous navigational and aesthetic issues, significantly enhancing user satisfaction in accessing cultural information interactively.